Hacking exposed 6 : network security secrets & solutions:Hacking exposed 6 - McClure, Stuart; Scambray, Joel.; Kurtz, George (New York : McGraw-Hill, 2009)
The term now extends beyond protecting the secrets of major corporations and governments to include the average consumer.our most sensitive information is stored online in vast quantities.
Includes index.
ma 04/05/2018
Keywords: Computer networks; Computer security; Data protection